The Effect of Methanol and Ethyl Acetate Extracts of Kirinyuh Stem (Eupatorium odoratum L.) on Antifungal Activity of Fusarium oxysporum: - Fika Pita Loka; Sabirin Matsjeh; Etika Dyah Puspitasari (Universitas Ahmad Dahlan, 2023)
Fusarium oxysporum is a fungus that has a negative role, namely causing moler disease or Fusarium wilt in shallot plants. The purpose of this study was to determine the effect of methanol and ethyl acetate extracts of kirinyuh stem (Eupatorium odoratum L.) on the antifungal activity of Fusarium oxysporum. This study used a complete randomized design (CRD) with 8 treatments, namely negative control, positive control, concentrations of 10%, 20%, 40%, 60%, 80%, 100% with 3 replicates. The activity test was conducted using the Kirby Bauer method. Data from the study were processed by analysis of variance (one way anova) and continued by Duncan's test. The results showed that methanol and ethyl acetate extracts of kirinyuh stems affect the antifungal activity of Fusarium oxysporum. Ethyl acetate extract is more active to inhibit Fusarium oxysporum fungi compared to methanol extract. The highest inhibition zone diameter in the methanol extract was at 100% concentration which was 7.5 mm and the lowest at 10% concentration which was 2.67 mm. The highest inhibition zone diameter in the ethyl acetate extract was at 100% concentration which was 12.33 mm and the lowest at 10% concentration which was 4.67 mm.